Influence of deposition time in CdTe thin film properties grown by Close-Spaced Sublimation (CSS) for photovoltaic application - Rahman K.S.; Harif M.N.; Rosly H.N.; Kamaruzzaman M.I.B.; Akhtaruzzaman M.; Alghoul M.; Misran H.; Amin N. (Elsevier B.V., 2023)
Cadmium Telluride (CdTe) thin films were grown on borosilicate glass substrates by close-spaced sublimation (CSS) at a pressure of 1.52 Torr in Ar ambient. CdTe thin films were sublimed at a source temperature of 625 C and substrate temperature of 595 C. In this study, the impact of various deposition times on the structural, morphological, topographical, electrical and optical properties of CdTe thin films has been explored to achieve high quality thin film absorber layer for solar cells applications. The crystalline structure, surface morphology, surface topology, electrical and optical properties of the films were examined by using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM), Hall Effect measurement and UVVis spectrophotometry, respectively. XRD investigation demonstrated that CdTe film shows polycrystalline nature pronounced with cubic zinc blende structure with a strong preferential (1 1 1) orientation. The FESEM images illustrated that the surface morphology and the average grain size of the films were dependent on the deposition times of CdTe thin films. AFM analysis revealed noteworthy changes in the film's surface roughness values for different deposition times. Carrier concentration was found in the order of 1013 cm?3. Band gap of CdTe thin film was found in the range 1.451.48 eV, which is suitable to be used in CdTe thin film solar cells. 2019 The Authors